Microstructure-sensitive investigation on the plastic deformation and damage initiation of amorphous particles reinforced composites. (10th May 2016) - Nafar Dastgerdi, J.; Marquis, G.; Anbarlooie, B.; Sankaranarayanan, S.; Gupta, M.
Abstract: In this paper, new analytical modeling and simulation methodology based on finite element method are proposed to study microstructure sensitivity of damage initiation and plastic deformation in amorphous particles reinforced Mg-composites. In this simulation methodology, composite microstructure has been discussed based on the real morphology considering the inclusions with their actual size, shape, spatial positioning, and in the exact amount. The main purpose of this study is to develop an in-depth understanding of relationship between the microstructure, plastic deformation and damage initiation of these novel light metal composites. Results indicate that when particles are closely associated in the cluster, the plastic flow of the matrix inside the cluster is constrained and would initiate only after plastic flow begins in the regions without clusters. The constraint of deformation will promote early the void formation in the matrix and interface debonding in the clustering region. Experimental findings show that there is a strong relationship between damage formation and the local volume fraction of the reinforcement. Moreover, the results of tensile testing and microstructural characterization clearly reveal that the distribution of reinforcement particles controls the extrusion load which obviously reflects the 0.2%YS of the composite samples.